In Vivo X‐ray Imaging of Transport of Renal Clearable Gold Nanoparticles in the Kidneys. Issue 43 (25th September 2017) - Xu, Jing; Yu, Mengxiao; Carter, Phoebe; Hernandez, Elizabeth; Dang, Andrew; Kapur, Payal; Hsieh, Jer‐Tsong; Zheng, Jie
Abstract: With more and more engineered nanoparticles (NPs) being designed renal clearable for clinical translation, fundamental understanding of their transport in the different compartments of kidneys becomes increasingly important. Here, we report noninvasive X‐ray imaging of renal clearable gold NPs (AuNPs) in normal and nephropathic kidneys. By quantifying the transport kinetics of the AuNPs in cortex, medulla and pelvis of the normal and injured kidneys, we found that ureteral obstruction not just blocked the NP elimination through the ureter but also slowed down their transport from the medulla to pelvis and enhanced the cellular uptake. Moreover, the transport kinetics of the NPs and renal anatomic details can be precisely correlated with local pathological lesion. These findings not only advance our understandings of the nano‐bio interactions in kidneys but also offer a new pathway to noninvasively image kidney dysfunction and local injuries at the anatomical level. Abstract : Imaging of nanoparticle transport : High‐contrast noninvasive X‐ray imaging of the transport process of renal clearable gold nanoparticles makes it possible to quantitatively understand the interactions between the nanoparticles and both a normal and an injured kidney at the anatomical level. The transport kinetics of the nanoparticles and renal anatomic details can be precisely correlated with local pathological lesion.